The Effects of Personality on a Subject's Information Processing: A Comment. - Pratt, Jamie (The Accounting Review, 1980)
The article presents comments of the author on a paper by W. McGhee, M. Shields and J. Birnberg, titled "The Effects of Personality on a Subject's Information Processing," published in the July 1998 issue of the journal "The Accounting Review." According to the author, McGhee, Sheilds and Birnberg are to be commended for their description of current research findings in the area of determinants of human decision-making. In the highly complex and relatively unexplored area of human information processing, accountants can certainly benefit from such literature reviews. Unfortunately, their theoretical discussion and experimental design do not reflect that literature review. It is questionable whether the research questions and associated empirical tests could have enlightened accountants regarding the information processing of financial accounting cues. Moreover, there is sufficient evidence to suggest that conclusions drawn by McGhee, Sheilds and Birnberg do not necessarily follow from results of their empirical tests.